Severe Influenza With Invasive Pulmonary Aspergillosis in Immunocompetent Hosts: A Retrospective Cohort Study - Duan, Yishan; Ou, Xinyan; Chen, Yusha; Liang, Binmiao; Ou, Xuemei (Frontiers in Medicine, 2021)
Background: Influenza was an independent risk factor for invasive pulmonary aspergillosis (IPA). In light of increasing incidence and mortality of influenza associated aspergillosis, our study summarized risk factors, clinical characteristics and prognostic factors of developing aspergillosis in immunocompetent hosts with influenza to further screen high-risk population and improve outcome. Background: Influenza was an independent risk factor for invasive pulmonary aspergillosis (IPA). In light of increasing incidence and mortality of influenza associated aspergillosis, our study summarized risk factors, clinical characteristics and prognostic factors of developing aspergillosis in immunocompetent hosts with influenza to further screen high-risk population and improve outcome. Method: We reviewed the patient characteristics, laboratory examinations, radiological imaging and microbiology data of 72 influenza patients with IPA and 84 influenza patients without IPA admitted to West China Hospital. Result: Our study shown that aspergillosis co-infection increased overall mortality of severe influenza from 22.6% to 52.8%, along with higher white blood count (WBC) (10.9±5.0 VS 8.4±3.3, P=0.016), Neutrophiles (9.5±5.0 VS 7.0±3.8, P=0.023), procalcitonin (PCT) (8.6±15.9 VS 1.2±2.1, P=0.009) and a lower CD4+T cell count(189.2±135.3 VS 367.1±280.0, P=0.022) in death group. No impact of age, gender, underlying diseases, immunosuppressive agents and steroids use, CD4+T cell count on incidence of influenza associated aspergillosis was observed. But influenza associated aspergillosis cases mostly accompanied with more H1N1 subtype (91.7% VS 79.8%, P=0.037) and higher level of C-reactive protein (CRP) (117.6±88.1 VS 78.5±75.2, P=0.017) and interleukin 6 (IL-6) (133.5±149.2 VS 69.9±100.0, P=0.021) than those without aspergillosis. Conclusion: Aspergillosis co-infection in severe influenza patients can lead to a significant increased mortality, which was associated with severe respiratory failure due to mixed infection and immunosuppression. Pulmonary excessive inflammatory response was related with IPA co-infection.